Towards a reliable seismic assessment of rocking components. (1st March 2021) - D'Angela, Danilo; Magliulo, Gennaro; Cosenza, Edoardo
Highlights: Critical assessment of methods for seismic evaluation of rocking components. Frequency content, velocity to acceleration ratio and input severity characterization. Reliability evaluation of protocols considering real ground motions as a reference. Technical recommendations towards a reliable seismic assessment of rocking components. Abstract: The paper addresses the reliability of the existing shake table testing protocols for assessment of the seismic response of freestanding, i.e. unanchored, components meant as rigid blocks; it is assumed that geometric and boundary conditions lead to rocking without sliding. The criticalities of the available assessment methods are primarily identified by correlating the rigid block motion to the features of the inputs derived according to the existing testing protocols. Numerical analysis of rigid blocks is performed to evaluate the planar dynamic response of a wide range of unanchored components subjected to base acceleration inputs in compliance with the reference protocols and considering a reference set of real strong ground motions (ATC63). The most referenced protocols for acceleration-sensitive components are considered, i.e., ICC-ES AC156 and FEMA 461; a sinusoidal protocol specifically aimed at freestanding (rigid) components is also taken into account. The reliability of the protocols is assessed by extending the structural reliability methods to the specific case. Recommendations towards a reliable assessment of rocking components are finally provided.